Combined Analysis of Volatile Terpenoid Metabolism and Transcriptome Reveals Transcription Factors Related to Terpene Synthase in Two Cultivars of Dendrobium officinale Flowers - Li, Ninghong; Dong, Yingxue; Lv, Min; Qian, Li; Sun, Xu; Liu, Lin; Cai, Yongping; Fan, Honghong (Frontiers in Genetics, 2021)
Dendrobium officinale is a kind of traditional Chinese herbal medicine. Its flowers could be used as health care tea for its aroma flavor and medicinal value. Most recent studies demonstrated that terpenoids are the main components of the aromatic compounds in the flowers, but the biosynthesis of terpenoids is poorly understood in D. officinale. In the experiment, the flowers from two cultivars of D. officinale with different smells were collected. The transcriptome analysis and combined volatile terpenoids determination were performed to identify the genes related to the biosynthesis of the terpenoids. The results showed that the different products of volatile terpenoids are α-thujene, linalool, α-terpineol, α-phellandrene, γ-muurolene, α-patchoulene, and δ-elemene in two cultivar flowers. The transcriptome analysis detected 25,484 genes in the flowers. And 18,650 differentially expressed genes were identified between the two cultivars. Of these genes, 253 genes were mapped to the terpenoid metabolism pathway. Among these genes, 13 terpene synthase (TPS) genes may have correlations with AP2/ERF, WRKY, MYB, bHLH, and bZIP transcription factors by weighted gene co-expression network analysis (WGCNA). The transcription factors have regulatory effects on TPS genes. These results may provide ideas for the terpenoid biosynthesis and regulatory network of D. officinale flowers.